The rate of compliance to seat belt usage among automobile drivers on three categories of roads in Nigeria: an observatory survey (2012)
Injuries to head, chest and abdomen are a major cause of death for unrestrained vehicle occupants, particularly the drivers. The use of seat belts therefore plays a significant role in reducing the severity of injuries. The study examined the compliance rate of seat belt use on different road hierarchies in Abeokuta (Nigeria) using an observatory method. Findings indicated that there was 54%, 37.3% and 13.6% compliance rate on three categories of roads studied. Also, females complied more with the use of seat belts on each of the roads with compliance rates at 43.3%, 47.2% and 50% compared with males who had 32.6%, 38.6% and 39.6% seat belt compliance rates. Chi-square analysis showed significant variations in the use of seat belt on the roads (p>0.05). The paper suggests increased awareness and enforcement of traffic laws among others in order to ensure sustainable use of seat belts among motorists in Nigeria.